Concentrations of aliphatic and polycyclic aromatic hydrocarbons in ambient PM2.5 and PM10 particulates in Doha, Qatar. (1st February 2019) - Javed, Wasim; Iakovides, Minas; Stephanou, Euripides G.; Wolfson, Jack M.; Koutrakis, Petros; Guo, Bing
ABSTRACT: Organic carbon (OC), elemental carbon (EC), and 90 organic compounds (36 polycyclic aromatic hydrocarbons [PAHs], 25  n -alkane homologues, 17 hopanes, and 12 steranes) were concurrently quantified in atmospheric particulate matter of PM2.5 and PM10 . The 24-hr PM samples were collected using Harvard Impactors at a suburban site in Doha, Qatar, from May to December 2015. The mass concentrations (mean ± standard deviation) of PM2.5 and PM10 were 40 ± 15 and 145 ± 70 µg m −3, respectively, exceeding the World Health Organization (WHO) air quality guidelines. Coarse particles comprised 70% of PM10 . Total carbonaceous contents accounted for 14% of PM2.5 and 10% of PM10 particulate mass. The major fraction (90%) of EC was associated with the PM2.5 . In contrast, 70% of OC content was found in the PM2.5–10 fraction. The secondary OC accounted for 60–68% of the total OC in both PM fractions, indicating photochemical conversions of organics are much active in the area due to higher air temperatures and solar radiations. Among the studied compounds, n -alkanes were the most abundant group, followed by PAHs, hopanes, and steranes. n -Alkanes from C25 to C35 prevailed with a predominance of odd carbon numbered congeners (C27 –C31 ). High-molecular-weight PAHs (5–6 rings) also prevailed, within their class, with benzo[ b  +  j ]fluoranthene (Bb + jF) being the dominant member. PAHs were mainly (80%) associated with the PM2.5 fraction. Local vehicular and fugitive emissions were predominant during low-speed southeasterly winds from urban areas, while remote petrogenic/biogenic emissions were particularly significant under prevailing northwesterly wind conditions. Implications : An unprecedented study in Qatar established concentration profiles of EC, OC, and 90 organic compounds in PM2.5 and PM10 . Multiple tracer organic compounds for each source can be used for convincing source apportionment. Particle concentrations exceeded WHO air quality guidelines for 82–96% of the time, revealing a severe problem of atmospheric PM in Doha. Dominance of EC and PAHs in fine particles signifies contributions from combustion sources. Dependence of pollutants concentrations on wind speed and direction suggests their significant temporal and spatial variability, indicating opportunities for improving the air quality by identifying sources of airborne contaminants.